Ir(bis-NHC)-Catalyzed Direct Conversion of Amines to Alcohols in Aqueous Glycerol - Cheong, Yeon Joo; Lee, Seunghyeon; Hwang, Sang Joon; Yoon, Woojin; Yun, Hoseop; Jang, Hye Young (European Journal of Organic Chemistry, 2019)
Sustainable catalytic conversion of amines to alcohols was realized in the presence of iridium catalysts and aqueous glycerol. Iridium catalysts involving bis-N-heterocyclic carbene (bis-NHC) show good reactivity and stability in the conversion of amines into alcohols in aqueous glycerol. The reaction was initiated with the dehydrogenation of amines and followed by hydrolysis and reduction. Iridium catalysts play dual roles in both the dehydrogenation and reduction steps. By employing glycerol as a solvent and hydrogen source, the final reduction was facilitated. The synthesis and characterization of various Ir(bis-NHC) complexes are described along with the catalytic reaction results of the amine into alcohol conversion.
Keywords: Alcohols; Amines; Dehydrogenation; Glycerol; Iridium